HISTORY AND ETHNOCULTURAL CHANGES OF THE KASHKADARYA ARABS - Ergasheva Yulduz Alimovna (American Journals Publishing, 2025)
The article analyzes the history of settlement, cultural traditions, customs, and processes of ethnocultural self-awareness of the Arabs of the Kashkadarya oasis of Uzbekistan. In addition, the processes of transformation in the homes and clothing of the Arabs, ethnic features in the family and family rituals, including innovations in this area and trends in the development of the ethnocultural identity of the Arabs in the years of independence are studied.
Keywords: Arabs, ethnic characteristics, economic and cultural traditions, customs, ethnocultural environment, traditions, ethnocultural identity.